The daily lives of Muslims Islam and public confrontation in contemporary Europe - Göle, Nilüfer 1953- (Zed Books, 2017)
For many in the West, Islam has become a byword for 'terrorism'. From 9/11 to the Paris attacks, our headlines are dominated by images of violence and extremism. Now, as the Western world struggles to cope with the refugee crisis, there is a growing obsession with the issue of Muslim integration. Those Muslims who fail to assimilate are branded the 'enemy within', with their communities said to provide a fertile breeding ground for jihadists. Such narratives, though, fail to take into account the actual lives of most Muslims living in the West, fixating instead on a minority of violent extremists. In 'The Daily Lives of Muslims', Nilüfer Göle provides an urgently needed corrective to this distorted image of Islam. Engaging with Muslim communities in 21 cities across Europe where controversies over 'integration' have arisen - from the banning of the veil in France to debates surrounding Sharia law in the UK - the book brings the voices of this neglected majority into the debate. In doing so, Göle uncovers a sincere desire among many Muslims to participate in the public sphere, a desire which is too often stifled by Western insecurity and attempts to suppress the outward signs of religious difference
First published in French in 2015 as Musulmans au quotidien : une enquête européenne sur les controverses autour de l'islam by Editions La Découverte, Paris, France. - Includes bibliographical references (pages 319-328) and index. - Translated from the French
Keywords: Muslims / Europe; Muslims / Social conditions / Europe; Muslims / Political activity / Europe; Islam and politics / Europe; Religious life / Islam; Islam and politics; Muslims; Muslims / Political activity; Muslims / Social conditions; Religious life / Islam / Europe